Pengaruh Gaya Hidup Hedonisme, Mental Accounting, E-Wallet, Locus Of Control Dan Literasi Keuangan Terhadap Pengelolaan Keuangan Mahasiswa - Mustafa Samir; Lia Rachmawati; Mainatul Ilmi (CV. ITTC INDONESIA, 2025)
Student financial management is an important issue given the high risk of consumptive behavior and difficulties in managing finances among the younger generation. This study aims to determine the influence of hedonic lifestyle, mental accounting, E-wallet, locus of control, and financial literacy on the financial management of students at the Mandala Institute of Technology and Science. This research method uses a quantitative approach with a total population of 1,135 FEB ITS Mandala students and uses random sampling technique so that 92 samples were obtained. Data was collected through questionnaires and processed using SPSS. The data analysis methods used were data quality testing, classical assumption testing, multiple linear regression analysis, R2 coefficient of determination analysis and hypothesis testing. The results show that mental accounting and locus of control have a partial effect on financial management. Meanwhile, hedonic lifestyle, E-wallet and financial literacy do not have a partial effect. Simultaneously, all variables significantly influence financial management.